2014
DOI: 10.1111/1756-185x.12415
|View full text |Cite
|
Sign up to set email alerts
|

Do statins reduce the cardiovascular risk in patients with rheumatoid arthritis?

Abstract: Objective: Patients with rheumatoid arthritis (RA) are at significantly higher risk of cardiovascular (CV) morbidity and mortality compared with the general population. Traditional CV risk factors cannot explain the total excess of CV morbidity and mortality in RA patients. At present, it is not clear whether treatment with statins might be of benefit in RA patients. The aim of the present systematic literature review is to summarize the published evidence concerning treatment with statins and its impact on CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 19 publications
0
29
0
Order By: Relevance
“…Two trials, TRACE (Trial of Atorvastatin for Primary Prevention of Cardiovascular Events in RA), which was stopped early due to low event rate, and its predecessor, TARA (Trial of Atorvastatin in RA), showed statistically significant arthritis and lipid-control effects of statins [91, 92]. Another trial reported better articular response in RA patients receiving tofacitinib plus atorvastatin compared to tofacitinib monotherapy [93].…”
Section: Introductionmentioning
confidence: 99%
“…Two trials, TRACE (Trial of Atorvastatin for Primary Prevention of Cardiovascular Events in RA), which was stopped early due to low event rate, and its predecessor, TARA (Trial of Atorvastatin in RA), showed statistically significant arthritis and lipid-control effects of statins [91, 92]. Another trial reported better articular response in RA patients receiving tofacitinib plus atorvastatin compared to tofacitinib monotherapy [93].…”
Section: Introductionmentioning
confidence: 99%
“…This persistent inflammatory response is also thought to be an underlying cause for the increased risk of developing CVD in patients with arthritis (1, 2). In this context, statins protect from CVD and recent studies suggest that they also reduce disease activity in patients with rheumatoid arthritis (411). It is evident that the pleiotropic actions of statins cannot be uniquely ascribed to inhibition of HMGCA reductase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study suggested that a TZD antidiabetic agent pioglitazone, i.e., a synthetic ligand of PPAR, could improve both insulin resistance and the disease activity in RA . Furthermore, statins [or hydroxymethylglutaryl‐coenzyme A (HMG‐CoA) reductase inhibitors] can be used in RA to reduce serum lipid levels as well as improve the RA disease activity, owing to their anti‐inflammatory effects , . However, there have been no clear demonstrations of the direct modulatory role of ANGPTL4 or other PPAR‐modulating agents in the disease activity or the incidence of human RA; therefore, further studies are warranted.…”
Section: Angptl‐4mentioning
confidence: 99%